Le tourisme des Antilles françaises saisi par le droit économique - Liroy, Axel (Université Côte d'Azur, 2020)
Objet à multiples dimensions juridiques – le commerce, la concurrence, la fiscalité, l’environnement, le salariat, l’urbanisme, les droits et libertés fondamentaux, la valorisation du folklore et des traditions, la formation, la police, la construction notamment –, le tourisme est le terrain de synergie d’acteurs et d’activités publics et privés en lien direct ou indirect avec l’économique. Un lien de subordination ordonnée caractérisé par la privation, relativement motivée, de l’acteur économique d’un accès libre et direct au marché. C’est l’office du pouvoir économique public. Aux Antilles françaises, il est l’artisan d’un protectionnisme juridique, irradiant, variablement éloigné des nécessités économiques par opposition franche à une Caraïbe plus libérale et lacunaire, aux méthodes distorsives de concurrence, éminemment connectée aux nécessités économiques. Propulsées dans la modernité du droit par leur nationalité politique et ses corollaires – il est une identité de droits entre les Antilles françaises, la France continentale et, résolument, l’Union européenne –, les Antilles françaises sont, au niveau de leur région d’extraction, marginales. La conjuration, au moins partielle, de leur marginalité et, par ricochet, de celle de leur tourisme passerait par un changement de paradigme obtenu notamment d’un mouvement de décentration (« sortir de soi »). Ce dernier tire sa subsistance d’une société devenue mondialisée et interdépendante exhortant les petites économies au regroupement pertinent. Un mouvement qui, matériellement confronté à l’ombre menaçante de l’assimilation juridique dans le cas des Antilles françaises, requiert une fine précision. L’intégration régionale, dont la formule contractuelle – méthode alternative d’organisation de l’économie –, en ses force, intensité, diversité, flexibilité et massivité, est la figure de proue, sans prétendre à la panacée, emporte un effet décentriste. Il naît du contrat économique, plus justement de sa force normative. Porté par l’acteur économique public – l’Etat et/ou ses démembrements territoriaux –, le traité ou l’accord international vise notamment la conduite de politiques communes telle qu’en matière environnementale, les optimisation et fluidité circulatoires – des personnes, des biens, des services –, la réduction des écarts de développement, la protection de la concurrence. Porté par l’acteur économique privé – l’exemple des parties à un contrat de franchise –, sous couvert de la poursuite de la satisfaction d’intérêts particuliers, il organise des rapports d’économie confinant au transfert de technologie, au partage de marque, au renforcement de l’offre et de la demande, à la diminution du coût de la vie par la réalisation d’économie d’échelle, de gamme notamment. Maîtrisé, l’effet décentriste de l’intégration régionale pourrait, dans une certaine mesure, constituer un outil efficace pour une économie durable du tourisme des Antilles françaises en marge ou, quand cela est possible, en alternative aux procédés traditionnels. Objet à multiples dimensions juridiques – le commerce, la concurrence, la fiscalité, l’environnement, le salariat, l’urbanisme, les droits et libertés fondamentaux, la valorisation du folklore et des traditions, la formation, la police, la construction notamment –, le tourisme est le terrain de synergie d’acteurs et d’activités publics et privés en lien direct ou indirect avec l’économique. Un lien de subordination ordonnée caractérisé par la privation, relativement motivée, de l’acteur économique d’un accès libre et direct au marché. C’est l’office du pouvoir économique public. Aux Antilles françaises, il est l’artisan d’un protectionnisme juridique, irradiant, variablement éloigné des nécessités économiques par opposition franche à une Caraïbe plus libérale et lacunaire, aux méthodes distorsives de concurrence, éminemment connectée aux nécessités économiques. Propulsées dans la modernité du droit par leur nationalité politique et ses corollaires – il est une identité de droits entre les Antilles françaises, la France continentale et, résolument, l’Union européenne –, les Antilles françaises sont, au niveau de leur région d’extraction, marginales. La conjuration, au moins partielle, de leur marginalité et, par ricochet, de celle de leur tourisme passerait par un changement de paradigme obtenu notamment d’un mouvement de décentration (« sortir de soi »). Ce dernier tire sa subsistance d’une société devenue mondialisée et interdépendante exhortant les petites économies au regroupement pertinent. Un mouvement qui, matériellement confronté à l’ombre menaçante de l’assimilation juridique dans le cas des Antilles françaises, requiert une fine précision. L’intégration régionale, dont la formule contractuelle – méthode alternative d’organisation de l’économie –, en ses force, intensité, diversité, flexibilité et massivité, est la figure de proue, sans prétendre à la panacée, emporte un effet décentriste. Il naît du contrat économique, plus justement de sa force normative. Porté par l’acteur économique public – l’Etat et/ou ses démembrements territoriaux –, le traité ou l’accord international vise notamment la conduite de politiques communes telle qu’en matière environnementale, les optimisation et fluidité circulatoires – des personnes, des biens, des services –, la réduction des écarts de développement, la protection de la concurrence. Porté par l’acteur économique privé – l’exemple des parties à un contrat de franchise –, sous couvert de la poursuite de la satisfaction d’intérêts particuliers, il organise des rapports d’économie confinant au transfert de technologie, au partage de marque, au renforcement de l’offre et de la demande, à la diminution du coût de la vie par la réalisation d’économie d’échelle, de gamme notamment. Maîtrisé, l’effet décentriste de l’intégration régionale pourrait, dans une certaine mesure, constituer un outil efficace pour une économie durable du tourisme des Antilles françaises en marge ou, quand cela est possible, en alternative aux procédés traditionnels.
Keywords: Antilles françaises; Droit économique; French West Indies; Intégration régionale; Legal Protectionism; Protectionnisme juridique; Tourism; Tourisme

La reporting extra-financier en voie de se faire : Une étude herméneutique de l’appropriation d’une comptabilité socio-environnementale - Carn, Clément (Université de Poitiers, 2020)
Le développement de la comptabilité socio-environnementale au cours des dernières années représente un profond changement dans le champ de la comptabilité. Ses promoteurs proposent d'intégrer des éléments concernant le développement durable dans la communication des entreprises. Cette situation offre la possibilité d'étudier les pratiques comptables à un moment où elles ne sont pas encore figées et font encore l'objet de controverses. Notre recherche profite de cette situation pour étudier les processus sociaux qui concourent à façonner les institutions comptables. Nous questionnons plus précisément l'intégration du processus d'appropriation de l'une de ces nouvelles méthodes comptables (la méthode CARE) dans la construction socio-historique. Cette recherche s'inscrit alors logiquement dans le cadre de la théorie de l'appropriation, à laquelle nous proposons d'ajouter une dimension herméneutique. En effet, c'est par cette dimension qu'il est possible d'étudier la compréhension d'un outil à partir des cadres d'interprétations hérités de l'histoire. Cette attention portée à l'historicité nous conduit à proposer une généalogie des méthodes de comptabilité socio-environnementale. Celle-ci nous permet de distinguer le cadre dominant de la comptabilité prométhéenne – qui a vocation à garantir le maintien d'une capacité de production – du cadre critique de la comptabilité orphique qui permet de maintenir les entités écologiques pour elles-mêmes. À partir de cette compréhension théorique, notre étude empirique permet de montrer que, malgré la sensibilité écologique des acteurs, une comptabilité orphique fait systématiquement l'objet de tentative de détournement. Nous en déduisons l'importance des préjugés néoclassiques, c'est-à-dire des précompréhensions de certains concepts au travers du cadre dominant. Les débats scientifiques et politiques semblent toutefois permettre de réduire ces préjugés et conscientiser les choix opérer par les acteurs.
Keywords: Appropriation theory; Comptabilité; Comptabilité socio-Environnementale; Ecological economics.; Environmental economics; Hermeneutics; Herméneutique; Socio-Environmental accounting; Sociologie de la comptabilité; Sociology of accounting; Théorie de l’appropriation; Économie de l'environnement; Économie de l’environnement; Économie écologique

Les saisies de comptes bancaires en matière civile et commerciale : études de droit international - Guerreiro, Elodie (Université Paris 1, 2020)
La thèse est une étude de droit international portant sur le droit français des saisies de comptes bancaires en matière civile et commerciale. Elle définit le principe de territorialité du droit (au sens subjectiviste, normativiste et savignien). Elle distingue l’aspect procédural de la saisie d’un compte bancaire (la signification) de ses aspects substantiels (injonction de communiquer des données, indisponibilité et/ou transfert du solde du compte bancaire). Par observation du droit positif, elle soutient qu’en chacun de ces aspects, ladite saisie commande l’application de principes (subjectivistes) de territorialité distincts (territorialité des voies d’exécution, territorialité des traitements de données, territorialité des opérations de paiement) ; que seule l’analyse différenciée de ces principes permet de comprendre le régime synthétique des saisies des comptes bancaires en droit international. Cette approche analytique est riche d’enseignements. D’un point de vue pratique, elle permet de dégager des conditions potentielles d’invalidité et/ou d’illégitimité des saisies françaises de comptes bancaires étrangers. Par ailleurs, elle contribue à l’étude du régime international : des significations réelles faites à, et des transferts de données réalisés au sein d’une, personne morale ; du statut réel du compte bancaire. D’un point de vue théorique, elle révèle l’existence de conflits hétérogènes de lois et suggère une méthode pour leur résolution ; elle exige que l’approche subjectiviste du droit international, la lecture personnaliste du compte bancaire et des opérations de paiement, et l’analyse fonctionnelle de la monnaie, soient présentées et développées.
Keywords: Bank accounts; Bank secrecy; Banques; Comptes bancaires; Comptes en banque; Conflict of laws (public law); Conflits de lois (droit public); Data processing; Droit international et droit interne; Droit international privé; Droit monétaire; France; Gouvernance des établissements de crédit; Governance of credit institutions; Mesures conservatoires; Money; Monnaie; Opérations de paiement; Payment transactions; Principe de territorialité; Protection de l'information (informatique) – France; Saisie conservatoire; Secret bancaire; Secret professionnel; Seizure proceeding; Service of process to legal entity; Signification à personne morale; Territoriality principle; Theories of international law; Théories du droit international; Traitement de données

Blockchain, criptoativos e os títulos circulatórios do Direito Comercial - Micheli, Leonardo Miessa De (Universidade de São Paulo, 2020)
Na presente tese, busca-se analisar o fenômeno da blockchain e dos criptoativos, desde sua perspectiva genética relacionada ao comportamento social que explicam e justificam seu surgimento e o exponencial crescimento de sua utilização, passando pelas características e soluções técnicas existentes e propostas para as tecnologias de registro distribuído, denominadas Distributed Ledger Technologies, ou simplesmente DLTs, para, finalmente, observar os instrumentos de reflexo econômico suportados em tais plataformas, aqui denominados títulos circulatórios, sob o ponto de vista teórico do Direito Comercial. Para tal objetivo, é proposta uma estruturação teórica sobre os criptoativos, sua natureza jurídica, classificação e o estudo de seu posicionamento em relação a outros institutos do direito, como a moeda, os valores mobiliários e os títulos de crédito, a fim de identificar possíveis enquadramento dos ativos virtuais na tutela jurídica já existente sobre tais tradicionais instrumentos, tanto por sua teoria quanto por sua regulação. Por fim, ainda são analisadas possíveis aplicações da infraestrutura blockchain na criação e circulação de títulos circulatórios tradicionais do Direito Comercial, como valores mobiliários e mercado de capitais, além dos títulos de crédito desmaterializados. Foram utilizadas para o desenvolvimento da pesquisa as metodologias exploratória e empírica, estruturando-se o conteúdo da tese de forma retórica por meio das seguintes grandes premissas: (i) por quê; (ii) como; e (iii) para quê, identificadas nos subtítulos dos 04 Capítulos como: Por que estas tecnologias disruptivas vieram para ficar? Como é possível a tecnologia conferir o elemento essencial da confiança? O que são e em que se aplicam os ativos virtuais e as redes descentralizadas? Quais outros usos das tecnologias de registro descentralizado podem ser úteis aos instrumentos circulatórios de Direito Comercial? Conclui-se, ao final da pesquisa, que a tutela dos criptoativos deve ser considerada com base na função econômica de cada espécie, conforme sugerido nas conclusões, adequando-se as respectivas tutelas regulatórias às peculiaridades de tais instrumentos, tanto genéticas quanto estruturais, sob pena de esvaziamento da própria causalidade existencial dos ativos virtuais.
Keywords: Banco de dados distribuídos; Blockchain; Brasil; China; Circulatory instruments; Criptologia; Crypto-assets; Cryptoactif; Cryptocurrencies; Currency; DLT; Dinheiro eletrônico; Direito Comercial; Direito Comparado; Droit commercial; Estados Unidos; Europa; Mercado de capitais; Moeda (Economia); México; Negotiable instruments; Securities; Título de crédito; Valeurs mobilières

Les enjeux managériaux des entreprises et des organisations culturelles en contexte de diversité culturelle : le cas du Cameroun. - Loembet, Eric (Université Paris-Saclay, 2020)
La question du développement des entreprises et des organisations culturelles (EOCs) s'est intégrée dans les discours des acteurs-entrepreneurs culturels, dans plusieurs pays africains en vue, d'une appropriation des normes les caractérisant. Un discours qui mérite une clarification dans un environnement fusionnant le formel et l'informel dans la création de richesses. Face à une diversité culturelle favorisant la croissance économique et le développement humain, la création des richesses devient une opportunité de rentabilité et du développement de l’économie culturelle, le cas du Cameroun. Ainsi, les EOCs deviennent et se présentent comme des outils de capitalisation des valeurs et des richesses économiques. À cet effet, analyser et évaluer le secteur de l'économie de la culture, c'est définir le rôle, l’importance et l’impact des EOCs à contribuer à la création de richesses et à la croissance économique au Cameroun. Moteur des échanges des biens et des services culturels, ainsi que des capitaux, les EOCs contribuent au développement de l'économie nationale (PIB). En prenant part active à la croissance économique intérieure d'une nation, elles apportent une valeur ajoutée dans la valorisation des richesses, dans la création d'emploi et le développement de l’humain. Le rôle très capital qu'elles jouent dans l'appropriation et la valorisation des richesses, détermine l'intérêt économique dans la créativité artistique et culturelle. De ces transformations qui agissent au sein des EOCs, il est question de déterminer les enjeux managériaux de développement en contexte de diversité culturelle au Cameroun. Ainsi, la réflexion de cette étude se fonde sur ce paradoxe de la pluralité des richesses et de sa faible contribution à la création de richesses, ainsi qu'au développement de l'économie de la culture camerounaise. The question of the development of enterprises and cultural organisations (EOCs) has been integrated into the discourse of actor cultural contractor in several African countries, with a view to appropriating the standards characterising them. A discourse which deserves clarification in an environment merging the formal and the informal in the creation of wealth. Faced with cultural diversity favoring economic growth and human development, the creation of wealth becomes an opportunity for profitability and the development of the cultural economy, the case of Cameroon. Thus, the EOCs become and present themselves as tools for capitalising on economic values and wealth. To this end, analysing and evaluating the cultural economy sector means defining the role, importance and impact of the EOCs in contributing to the creation of wealth and economic growth in Cameroon. Driving the exchange of cultural goods and services, as well as capital, the EOCs contribute to the development of the national economy. By taking an active part in the internal economic growth of a nation, they bring added value in the valuation of wealth, in job creation and human development. the very crucial role that they play in the appropriation and enhancement of wealth, determines the economic interest in artistic and cultural creativity. of these transformations that are taking place within the EOCs, it’s a question of determining the managerial stakes of development in the context of cultural diversity in Cameroon. the reflection of this study will be based on this paradox of the plurality of wealth and it’s low contribution to the creation of wealth, as well as to the development of the economy of Cameroonian culture.
Keywords: Cameroon; Cameroun; Cultural Diversity; Cultural Enterprises; Cultural and Creative; Culture; Diversité culturelle; Diversité culturelle – Cameroun; Economics of Culture; Economie de la culture; Enjeux managériaux; Entreprises (développement); Entreprises culturelles; Industries culturelles; Industries culturelles et créatives; Managerial Issues

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Protesto notarial no âmbito do contrato de mútuo bancário - Santos, Reinaldo Velloso dos (Universidade de São Paulo, 2020)
As instituições financeiras exercem um papel de extrema relevância na economia contemporânea, intermediando recursos para concessão de crédito à produção e ao consumo. Para melhor desempenhar essa função precisam de meios que assegurem o cumprimento das obrigações. Dentre esses meios está o protesto notarial, ato de incumbência de um profissional do Direito dotado de fé pública, que documenta solenemente a manifestação da insatisfação do credor, sendo revestido de ampla publicidade. É precedido de intimação do devedor, a quem se concede a oportunidade de voluntariamente adimplir a obrigação. Esse instituto, arraigado na tradição jurídica brasileira, tem-se revelado como uma alternativa ao processo judicial, permitindo a recuperação do crédito de forma mais célere e com custo reduzido. No trabalho é apresentado um panorama dos contratos bancários, incluindo o mútuo, bem como do protesto notarial. Além disso, trata dos principais aspectos relativos ao protesto do contrato de mútuo bancário e da cédula de crédito bancário. Ao final, são apresentadas reflexões do autor sobre o tema. As características peculiares do protesto notarial reforçaram seu papel histórico no Brasil. E as recentes modificações na disciplina do instituto certamente contribuirão para sua utilização de forma mais eficiente pelas instituições financeiras, com a perspectiva de redução das taxas nos empréstimos, beneficiando a produção e circulação de riquezas e, por conseguinte, permitindo o desenvolvimento econômico do país. Financial institutions play a relevant role in contemporary economy, by intermediating credit facilities for production and consumption. Availability of efficient enforcement measures is of the essence in such process. Among these providences is the protest, which consists on a formal proof of dishonor, drawn by a public notary, who is a legal professional vested with public faith. Information about protests is public and can be provided to anyone. The notary sends prior notice to the debtor, thus offering a last opportunity to pay the overdue amount to prevent the protest. This institution, rooted in the Brazilian legal tradition, became an alternative to judicial procedure, making the protest a quick and inexpensive debt recovery tool. This thesis presents an overview of banking agreements, including loans, as well as the notarial protest. In addition, the main aspects related to the protest of loan agreements and the cédula de crédito bancário - a negotiable instrument issued by the borrower - are also contained herein. At the end, the author presents his reflections on the topic. The peculiar characteristics of the notarial protest reinforced its historical role in Brazil. And the recent regulatory changes will certainly contribute to increase the protest's effectiveness, especially for financial institutions, with the prospect of reducing interest rates in loan agreements, thus benefiting the production and circulation of wealth, and bringing forth economic development to Brazil.
Keywords: Banking agreement; Banking loan; Contrat; Contrato bancário; Default; Direito notarial; Inadimplemento das obrigações; Notarial law; Notarial protest; Protesto de título; Protêt notarié; Prêt bancaire

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Essais sur l'efficience et la fiscalité pétrolière dans les pays en développement - Gab-Leyba, Guy Dabi (Université Clermont Auvergne, 2020)
L’objectif de cette thèse est de mettre en évidence les déterminants de l’efficience des politiques publiques dans les pays en développement. Les résultats relèvent que les pays dotés de ressources naturelles et en situation de fragilité ont tendance à avoir des dépenses publiques d’éducation primaires moins efficientes. Les résultats révelent aussi que l’accroissement de la part des dépenses de santé dans les dépenses totales des ménages, du taux d’incidence de la pauvreté, du taux d’alphabétisation et la localisation en zone considérée comme austère réduisent l’efficience des structures de santé. A l’inverse, la hausse du taux d’incidence du paludisme, du taux de prévalence de la malnutrition améliorent l’efficience des structures de santé. S’agissant de l’efficience des établissements de crédits, les résultats mettent en exergue une amélioration du score d’efficience sur la période 2000-2015 en dépit du fait qu’en moyenne, l’efficience des banques de la zone CEMAC se situe autour de 33 %. Les estimations montrent aussi qu’une taille importante et une forte liquidité améliorent l’efficience technique des établissements de crédits tandis qu’un accroissement du risque bancaire la réduit. Enfin, l’évaluation des régimes fiscaux pétroliers en application au Tchad révèle que les contrats de partage de production permettent à l’Etat de capter une part plus importante de la rente pétrolière comparativement aux contrats basés sur le système de concession. En outre, les contrats basés sur le partage de production présentent la caractéristique d’être progressif. Ces résultats ont des implications en matière de politique économiques. Ainsi, les pays en developpement devraient en priorité améliorer la qualité des dépenses sociales en promouvant la transparence et la bonne gouvernance dans la mise en œuvre des projets de developpement et politiques publiques. En particulier, dans le secteur de la santé, il est urgent d’améliorer la qualité du personnel de santé et une meilleure programmation des dépenses de fonctionnement visant à rendre les infrastructures de santé opérationnelles. Ensuite, pour accroitre la rentabilté des banques dans les pays de la zone CEMAC, il conviendrait de diversifier les structures bénéficiaires des crédits et mettre en œuvre des réformes visant à améliorer le climat des affaires. Enfin, le Gouvernement tchadien devrait réactiver une politique contra-cyclique en vue de se prémunir des fluctuations des recettes pétrolières. The aim of this thesis is to highlight the determinants of the efficiency of public policies in developing countries. The results show that countries with natural resources and in fragile situations tend to have less efficient public spending on primary education. The results also reveal that the increase in the share of health expenditure in total household expenditure, the poverty incidence rate, the literacy rate and the location in areas considered as isolated reduce the efficiency of health structures. Conversely, the increase in the incidence rate of malaria and the prevalence rate of malnutrition improve the efficiency of health structures. Regarding the efficiency of credit institutions, the results highlight an improvement in the efficiency score over the period 2000-2015 despite the fact that on average, the efficiency of banks in the CEMAC zone is around 33%. Estimates also show that a large size and high liquidity improve the technical efficiency of credit institutions while an increase in banking risk reduces it. Finally, the assessment of petroleum tax regimes in force in Chad reveals that production sharing contracts allow to Government to capture a higher share of oil rent compared to contracts based on the concession system. In addition, contracts based on production sharing have the characteristic of being progressive. These results have implications for economic policy. Thus, developing countries should give priority to improving the quality of social spending by promoting transparency and good governance in the implementation of development projects and publics policy. In particular, in the health sector, there is an urgent need to improve the quality of health personnel and better programming of operating expenditure aimed at making health infrastructures operational. Then, to increase the profitability of the banks in the countries of the CEMAC zone, it would be advisable to diversify the structures beneficiary of the credits and to implement reforms aiming at improving the business environment. Finally, the Chadian Government should reactivate a counter-cyclical policy in order to guard against fluctuations in oil revenues.
Keywords: Cash flow model; Concession contrat; Contrat de concession; Contrat de partage de production; Dépenses publiques; Education; Efficency; Efficience; Health; Impôts; Industrie et commerce; Modèle de flux de trésorerie; Natural ressources; Order m; Pays en voie de développement; Politique fiscale; Politique publique; Production sharing contrat; Public spending; Pétrole (exploitation); Ressources naturelles; SFA; Santé

La dématérialisation des valeurs mobilières en zone CEMAC - N'Tchatat Tounya, Fabrice Léonel (Université de Yaoundé 2, 2020)
La dématérialisation des valeurs mobilières a été amorcée par l’OHADA depuis son Acte Uniforme de 1997 où le mécanisme qui jusque-là n’était optionnel que pour les sociétés faisant appel public à l’épargne, a été étendu à toutes les valeurs émises dans l’espace OHADA de façon obligatoire en faveur de l’Acte Uniforme de 2014. Cette réforme d’envergure a également été posée en zone CEMAC de manière ambivalente. D’un côté par le règlement communautaire N° 01/14 du 25 avril 2014 qui limite la portée de cette dématérialisation aux valeurs mobilières qui sont émises dans le cadre d’un appel public à l’épargne et de l’autre par la loi camerounaise N° 2014/007 du 23 avril 2014 et son décret d’application N° 2014/3763 du 17 novembre 2014, ainsi que la loi gabonaise n°027/2016 du 06 février 2017 fixant le régime de la dématérialisation des valeurs mobilières en République Gabonaise qui étendent la dématérialisation à toutes les valeurs mobilières émises sur le territoire national. Aux termes de l’article 1er alinéa 2 de la loi camerounaise précédemment citée, la dématérialisation des valeurs mobilières est une opération de substitution des certificats physiques des titres, par l’inscription en compte des titres sous forme électronique. Il s’agit d’une révolution économique qui facilite la circulation et la conservation des titres, initialement détenus sous la forme matérielle. La dématérialisation des valeurs mobilières est un processus, elle est donc prescriptible. C’est-à-dire que sa mise en œuvre est limitée dans le temps. Ainsi, compte tenu du fait que la dématérialisation est une opération délicate, qui a une échéance et qui affecte le régime juridique des valeurs mobilières, l’étude d’un tel sujet invite à s’interroger sur les effets de la dématérialisation sur les valeurs mobilières et la pertinence des normes ayant vocation à les encadrer dans la sous-région tant dans sa mise en œuvre que dans la gestion des valeurs mobilières dématérialisées. Cette réflexion trouve tout son sens dans la mesure où d’une part, le législateur communautaire restreint le mécanisme de dématérialisation des valeurs mobilières tandis que les législateurs nationaux en font une portée large. D’autre part, les législateurs tant communautaire que nationaux ont ficelés les modalités de dématérialisation sans prendre en compte les réalités de l’activité économique sous régionale telle que l’inexistence des titres physiques. Enfin, à l’instar de l’AUDSCGIE du 30 janvier 2014, les textes en vigueur dans la sous-région rendent désormais obligatoire le régime d’inscription en compte des valeurs mobilières, lequel n’est pas sans effet sur le mode de détention et de circulation de celles-ci en zone CEMAC. The dematerialization of securities has been initiated by OHADA since its Uniform Act of 1997 where the mechanism which until then was optional only for companies making public offerings, has been extended to all the securities issued in the OHADA area on a mandatory basis in favor of the Uniform Act of 2014. This major reform was also applied in the CEMAC zone in an ambivalent manner. On the one hand by Community regulation N ° 01/14 of April 25, 2014 which limits the scope of this dematerialization to transferable securities which are issued within the framework of a public offering and on the other by law Cameroonian N ° 2014/007 of April 23, 2014 and its implementing decree N ° 2014/3763 of November 17, 2014, as well as the Gabonese law n ° 027/2016 of February 06, 2017 establishing the dematerialization regime for securities in Gabonese Republic which extend the dematerialization to all the securities issued on the national territory. Under the terms of article 1, paragraph 2, of the Cameroonian law cited above, the dematerialization of securities is a substitution operation for the physical certificates of the securities, by registering the securities in electronic form. It is an economic revolution which facilitates the circulation and conservation of securities, initially held in physical form. The dematerialization of securities is a process, so it can be prescribed. That is to say, its implementation is limited in time. Thus, given the fact that dematerialization is a delicate operation, which has a deadline and which affects the legal regime of transferable securities, the study of such a subject invites us to wonder about the effects of dematerialization on securities and the relevance of the standards intended to guide them in the sub-region both in its implementation and in the management of dematerialized securities. This reflection finds all its meaning insofar as, on the one hand, the Community legislator restricts the mechanism of dematerialization of securities while the national legislators make a broad scope of it. On the other hand, both Community and national legislators have tied up the dematerialization modalities without taking into account the realities of sub-regional economic activity such as the absence of physical titles. Finally, like the AUDSCGIE of January 30, 2014, the texts in force in the sub-region now make compulsory the system of registration in securities account, which is not without effect on the method of holding and circulation of these in the CEMAC zone.

Deveres de informação e adequação: responsabilidade civil dos intermediários financeiros - Paiva, Rafael Bianchini Abreu (Universidade de São Paulo, 2020)
O objetivo desta tese é apresentar, em perspectiva comparada entre Brasil e União Europeia, quais deveres devem ser impostos aos intermediários financeiros para que seus clientes não profissionais adquiram produtos e serviços adequados aos seus conhecimentos, experiências, necessidades, objetivos e situação financeira e, em caso de descumprimento desses deveres, as hipóteses e a extensão da responsabilidade civil dos intermediários financeiros. Nesse sentido, a crise financeira internacional de 2008 foi um divisor de águas por evidenciar problemas na distribuição de diversos instrumentos financeiros e resultar em diversos processos administrativos e judiciais, bem como reação de reguladores em diferentes jurisdições. Este trabalho está dividido em quatro Capítulos, cuja estrutura é a seguinte: I. Processo decisório e mercados financeiros: 1. As decisões individuais segundo a Teoria Neoclássica; 2. Risco, retorno e a Hipótese dos Mercados Eficientes (HME); 3. Falhas de mercado; 4. Racionalidade limitada: vieses cognitivos e emocionais do processo decisório; 5. Agentes quase racionais e Hipótese da Instabilidade Financeira (HIF); II. Intermediação e inovações financeiras: 1. A atividade de intermediação financeira; 2. Inovações financeiras de primeira geração e ciclo de endividamento privado; 3. Inovações financeiras recentes: moeda eletrônica, pagamentos instantâneos, criptoativos e stablecoins; III. Deveres de informação e adequação (suitability): 1. Princípios gerais e recomendações das organizações internacionais; 2. Deveres de informação e adequação na União Europeia; 2.1. Antes da crise financeira de 2008; 2.2. Reformas a partir da crise financeira de 2008; 3. Deveres de informação e adequação no Brasil; 3.1 Crédito rotativo; 3.2 Jurisprudência; 3.3 Decisões da CVM; IV. Responsabilidade civil. Considerações finais.
Keywords: Complex financial products; Cryptoassets; Cryptocurrencies; Dinheiro eletrônico; E-money; Financial innovations; Financial institutions; Instituição financeira; Intermédiaire financier; Marché financier; Mercado financeiro; Responsabilité civile; Stablecoins; Suitability

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework